2019
DOI: 10.1017/s2045796019000167
|View full text |Cite
|
Sign up to set email alerts
|

Reducing mental health-related stigma among medical and nursing students in low- and middle-income countries: a systematic review

Abstract: Aims This systematic review compiled evidence on interventions to reduce mental health-related stigma among medical and nursing students in low- and middle-income countries (LMICs). Primary outcomes were stigmatising attitudes and discriminatory behaviours. Methods Data collection included two strategies. First, previous systematic reviews were searched for studies that met the inclusion criteria of the current review. Second, a new search was done, covering the time since the previous reviews, i.e. January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 41 publications
1
52
0
1
Order By: Relevance
“…Recent studies demonstrated that undergraduate nursing students often encounter emotional problems due to academic stress [18,5]. The underlying stressors include frequent academic assessment and disparity between academic studies and medical practice, which often will affect the outcome of nursing training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that undergraduate nursing students often encounter emotional problems due to academic stress [18,5]. The underlying stressors include frequent academic assessment and disparity between academic studies and medical practice, which often will affect the outcome of nursing training.…”
Section: Discussionmentioning
confidence: 99%
“…Students who often feel overwhelmed by study burnout are more likely to fail in exams due. It is well known that psychological health has a positive impact on sustainable competitiveness, and is negatively correlated with study burnout [5]. Studies have also examined the effect of rumination on the psychological health of students [6].…”
Section: Introductionmentioning
confidence: 99%
“…These difficulties contribute to, and are compounded by, the association of mental illness with societal stigma (Carrara et al, 2019;Charette-Dussault and Corbière, 2019;Heim et al, 2019). Improved communication among researchers, clinicians, patient communities, and the public may mitigate stigma by conveying that mental illness is a brain disease, and not fundamentally different from ailments that affect other organs of the body, such as heart or kidney disease.…”
Section: Destigmatizing and Improving Communication On Mental Illnessmentioning
confidence: 99%
“…It is important to carefully assess the attitudes and behaviors of nursing students towards people with mental illness and to correct negative ones before their first contact in psychiatric training to ensure that students have more positive experiences [23]. Furthermore, student nurses and other healthcare students are the future mental health professionals and have the potential for changing the future of mental healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known on effective approaches to correct these negative attitudes and behaviors [10] [23], despite the previous reviews [10] [23] [26]- [36] that have shown that contact-based interventions have demonstrated positive attitudinal and behavioral changes for nursing students towards people with mental illness. The following is a brief description of the aim and focus of these previous reviews.…”
Section: Introductionmentioning
confidence: 99%